2015
DOI: 10.1111/avsc.12182
|View full text |Cite
|
Sign up to set email alerts
|

Does vegetation in restored salt marshes equal naturally developed vegetation?

Abstract: Question Do low stone dams built to prevent erosion and to restore salt marshes through increased sedimentation affect plant species composition? Location Dutch Wadden Sea area (ca. 53°N 5°E). Methods Relevés (N = 170) were made of the vegetation of two restored salt marsh sites on the barrier islands Terschelling (Grië) and Ameland (Neerlands Reid). Existing relevés of salt‐marsh vegetation (N = 6198) made along the entire Dutch Wadden Sea coast (both the mainland and the barrier islands) were used as a refer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
0
7
0
1
Order By: Relevance
“…Mid‐ and high‐marsh species occurred at lower elevations, supporting experimental studies showing that species’ lower elevation limits can also be controlled by competition (Bockelmann & Neuhaus, ). Intriguingly, while MRs often show significant differences in vegetation from natural marshes (Mossman et al., ; Wolters et al., ), sites restored by encouraging sedimentation through the use of bunds (more closely replicating sedimentary and successional conditions of natural saltmarshes) have developed equivalent vegetation (Van Loon‐Steensma, Van Dobben, Slim, Huiskes, & Dirkse, ). This may indicate that availability of bare sediment at high elevations during restoration (Figure S1) leads to marshes restored by MR following an inhibition successional model rather than a facilitation model (Connell & Slatyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mid‐ and high‐marsh species occurred at lower elevations, supporting experimental studies showing that species’ lower elevation limits can also be controlled by competition (Bockelmann & Neuhaus, ). Intriguingly, while MRs often show significant differences in vegetation from natural marshes (Mossman et al., ; Wolters et al., ), sites restored by encouraging sedimentation through the use of bunds (more closely replicating sedimentary and successional conditions of natural saltmarshes) have developed equivalent vegetation (Van Loon‐Steensma, Van Dobben, Slim, Huiskes, & Dirkse, ). This may indicate that availability of bare sediment at high elevations during restoration (Figure S1) leads to marshes restored by MR following an inhibition successional model rather than a facilitation model (Connell & Slatyer, ).…”
Section: Discussionmentioning
confidence: 99%
“…Conducting an active recovery project guides the path of the intervention, but also has an influence over its results, whether in terms of the species pool or the possibility of colonization (Doody, 2008;Hughes et al, 2009). Despite almost 60% of similarity index, post-intervened salt marsh documented by Van Loon-Steensma et al (2015) revealed a reduction in halophytes diversity, which relates to a great penetration of freshwater communities into the managed site, but also with a reduction of ruderal species.…”
Section: Discussion: Recovery or Restoration?mentioning
confidence: 99%
“…Managed salt marshes frequently report to old deembankments where marshes were reclaimed for agricultural usages Wolters et al (2005Wolters et al ( , 2008 and therefore there is a need to give back the ecosystem's natural state. This process is held by decision makers and is policy oriented towards specific objectives, as tidal reactivation (Byers and Chmura, 2007;Davy et al, 2011) or the opposite as building a stone barrier to prevent erosion, and strangle the tidal flow (Van Loon-Steensma et al, 2015). The Similarity indexes performed to evaluate the degree of resemblance between species of different recovery processes showed that in the cases of managed salt marshes, the indexes are endemically lower that those performed to unmanaged salt marshes (see Table 3).…”
Section: Similarity Indexesmentioning
confidence: 99%
“…However, as mentioned in the former paragraph, it is very difficult to value the nature and biodiversity, landscape and cultural-heritage benefits derived from the salt-marsh foreland. When there are no differences between vegetation of a natural salt-marsh and the vegetation of the foreland, then the difference in saltmarsh area between a flood defence system with and without a vegetated foreland may form an indicator for the benefits for nature and biodiversity [47].…”
Section: Benefits Of Risk Reduction By a Flood Protection System Of Amentioning
confidence: 99%